1998
DOI: 10.1111/j.2044-8279.1998.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Field independence, cultural context and academic achievement: a commentary

Abstract: Background. This review of literature on cross‐cultural aspects of perceptual disembedding skills takes as a starting point a commentary on the Spanish work on field dependence‐independence and scholastic achievements (Tinajero & Páramo, 1997). Aims. To place findings from cross‐cultural psychology on field independence in the context of current literature on multicultural education. Methods. A review of literature, and in particular a review of the authors' studies in this field. Results. It appears that beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In general, field-independent people are higher in their academic achievement than are field-dependent people (e.g., Bagley and Mallick, 1998;Mansfield, 1998; see also Jonassen and Grabowski, 1993 for a comprehensive review). Since the late 1970s and early 1980s, the FDI construct has become more and more widely examined in the context of learners' achievement under computer-assisted instructional conditions.…”
Section: Field-dependence/independence and The Group Embedded Figuresmentioning
confidence: 98%
“…In general, field-independent people are higher in their academic achievement than are field-dependent people (e.g., Bagley and Mallick, 1998;Mansfield, 1998; see also Jonassen and Grabowski, 1993 for a comprehensive review). Since the late 1970s and early 1980s, the FDI construct has become more and more widely examined in the context of learners' achievement under computer-assisted instructional conditions.…”
Section: Field-dependence/independence and The Group Embedded Figuresmentioning
confidence: 98%
“…In the field of education, numerous studies have found that thinking styles have implications for academic activities or performance (e.g., Bagley & Mallick, 1998;Bernardo et al, 2002;Betoret, 2007;Cano-Garcia & Hughes, 2000;Cilliers & Sternberg, 2001;Gurpinar et al, 2010;Khasawneh et al, 2006;Liu et al, 2008;Luk, 1998;Zhang, 2001Zhang, , 2002bZhang, , 2002dZhang, , 2004bZhang, , 2004cZhang, , 2006aZhang, , 2006bZhang, , 2007Zhang, , 2008Zhang & Sternberg, 1998, 2000.…”
Section: Thinking Styles and Academic Achievement Among Studentsmentioning
confidence: 99%
“…In the literature, the Sternberg's TSI (thinking style inventory) has been one of the most commonly used measurement tool among students. Researchers have examined the thinking styles in many variables, including achievement (Bagley & Mallick, 1998;Bernardo et al, 2002;Cano-Garcia & Hughes, 2000;Luk, 1998;Zhang, 2001Zhang, , 2002dZhang, , 2004bZhang, , 2006aZhang, , 2007Zhang, , 2008Zhang & Sternberg, 1998), learning and approach (Betoret, 2007;Zhang, 2004a;Zhang & Sternberg, 2000), personality traits (Zhang, 2000;2002c), psychosocial development (Zhang, 2002a), etc.. However, as Betoret (2007) asserted, studies of the relationship between thinking styles and students' satisfaction are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…They have also presented challenges to some of the stereotypical views about particular cultural groups. These challenges pertain to claims that: (1) Black and Hispanic (including Mexicans, Puerto Ricans, Cubans, and people of other Hispanic origin) students have a higher preference for the surface approach to learning (see Watkins and Mboya, 1997); (2) Asian students are rote learners; (3) Black and Hispanic students are more field dependent than are Anglo-American students; (4) students from group-oriented societies tend to be more field dependent than students from individualistically oriented societies (see Bagley and Mallick, 1998); and (5) students from group-oriented cultures are more norm-conforming in their thinking styles (see Sternberg, 1997). The challenges to the first two claims (1 and 2) are the result of research based on Biggs' (1978) construct of learning approaches.…”
Section: Intellectual Styles and Culturementioning
confidence: 99%
“…For example, Buriel's (1978) comparative study found no difference in the level of field dependence/ independence between Anglo-American and Mexican-American school children. In a review of the literature, Bagley and Mallick (1998) concluded that, compared with their Western counterparts (in this case, students from Canada, the UK, and the US), students from group-oriented cultures (in this case, Chinese and Japanese cultures) were more field independent.…”
Section: Field Dependence/independencementioning
confidence: 99%